Multivariate GWAS of Structural Dental Anomalies and Dental Caries in a Multi-Ethnic Cohort - Alotaibi, Rasha N.; Howe, Brian J.; Moreno Uribe, Lina M.; Valencia Ramirez, Consuelo; Restrepo, Claudia; Deleyiannis, Frederic W. B.; Padilla, Carmencita; Orioli, Ieda M.; Buxó, Carmen J.; Hecht, Jacqueline T.; Wehby, George L.; Neiswanger, Katherine; et al. (Frontiers in Dental Medicine, 2022)
Odontogenesis is a complex process, where disruption can result in dental anomalies and/or increase the risk of developing dental caries. Based on previous studies, certain dental anomalies tend to co-occur in patients, suggesting that these traits may share common genetic and etiological components. The main goal of this study was to implement a multivariate genome wide association study approach to identify genetic variants shared between correlated structural dental anomalies and dental caries. Our cohort (N= 3,579) was derived from the Pittsburgh Orofacial Clefts Study, where multiple dental traits were assessed in both the unaffected relatives of orofacial cleft (OFC) cases (n=2187) and unaffected controls (n=1392). We identified four multivariate patterns of correlated traits in this data: tooth agenesis, impaction, and rotation (AIR); enamel hypoplasia, displacement, and rotation (HDR); displacement, rotation, and mamelon (DRM); and dental caries, tooth agenesis and enamel hypoplasia (CAH). We analyzed each of these four models using genome-wide multivariate tests of association. No genome-wide statistically significant results were found, but we identified multiple suggestive association signals (P < 10-5) near genes with known biological roles during tooth development, including ADAMTS9 and PRICKLE2 associated with AIR; GLIS3, WDR72, and ROR2 associated with HDR and DRM; ROBO2 associated with DRM; BMP7 associated with HDR; and ROBO1, SMAD2 and MSX2 associated with CAH. This is the first study to investigative genetic associations for multivariate patterns of correlated dental anomalies and dental caries. Further studies are needed to replicate these results in independent cohorts.